Virulence‐associated protein A from Rhodococcus equi is an intercompartmental pH‐neutralising virulence factor. (9th November 2018) - von Bargen, Kristine; Scraba, Mirella; Krämer, Ina; Ketterer, Maren; Nehls, Christian; Krokowski, Sina; Repnik, Urska; Wittlich, Michaela; Maaser, Anna; Zapka, Pia; Bunge, Madeleine; Schlesinger, Martin; et al.
Abstract: Professional phagocytic cells such as macrophages are a central part of innate immune defence. They ingest microorganisms into membrane‐bound compartments (phagosomes), which acidify and eventually fuse with lysosomes, exposing their contents to a microbicidal environment. Gram‐positive Rhodococcus equi can cause pneumonia in young foals and in immunocompromised humans. The possession of a virulence plasmid allows them to subvert host defence mechanisms and to multiply in macrophages. Here, we show that the plasmid‐encoded and secreted virulence‐associated protein A (VapA) participates in exclusion of the proton‐pumping vacuolar‐ATPase complex from phagosomes and causes membrane permeabilisation, thus contributing to a pH‐neutral phagosome lumen. Using fluorescence and electron microscopy, we show that VapA is also transferred from phagosomes to lysosomes where it permeabilises the limiting membranes for small ions such as protons. This permeabilisation process is different from that of known membrane pore formers as revealed by experiments with artificial lipid bilayers. We demonstrate that, at 24 hr of infection, virulent R . equi is contained in a vacuole, which is enriched in lysosome material, yet possesses a pH of 7.2 whereas phagosomes containing a vapA deletion mutant have a pH of 5.8 and those with virulence plasmid‐less sister strains have a pH of 5.2. Experimentally neutralising the macrophage endocytic system allows avirulent R . equi to multiply. This observation is mirrored in the fact that virulent and avirulent R . equi multiply well in extracts of purified lysosomes at pH 7.2 but not at pH 5.1. Together these data indicate that the major function of VapA is to generate a pH‐neutral and hence growth‐promoting intracellular niche. VapA represents a new type of Gram‐positive virulence factor by trafficking from one subcellular compartment to another, affecting membrane permeability, excluding proton‐pumping ATPase, and consequently disarming host defences.